Peran kepemilikan manajerial dalam memoderasi tingkat utang, ukuran perusahaan dan persistensi laba - Dade Nurdiniah; Chita Oktapriana (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2023)
This study aims to analyze the role of managerial ownership in moderating leverage, firm size, and earnings persistence. The research was conducted by manufacturing companies listed on the Indonesia Stock Exchange. The sample selection used purposive sampling criteria, while the data analysis used in this study was multiple regression and moderated regression analyses. Before analyzing the data, first, perform the classical assumption test; after the data is declared to meet the test criteria, then a hypothesis test is carried out consisting of multiple regression analysis, coefficient of determination test, simultaneous significance test, partial significance test, and moderated regression analysis test. The results showed that leverage positively affected earnings persistence, firm size did not affect persistence, and managerial ownership could not moderate or weaken the effect of leverage and firm size on earnings persistence. Public interest statement This research can provide input for companies, especially in managing companies to generate profits; the profits generated must look stable or persistent because persistent profits can reduce investor anxiety about their investment decisions.